Protection of the Rights of Adultery Children in Indonesia: A Perspective of Positive and Islamic Law - Iffah Fathiah; Sofyan Mei Utama; Diana Farid; Husni Abdulah Pakarti, Muhammad; Al Kautsar Mabruri, Kemal; Hendriana, Hendriana (Hukum Keluarga Islam IAIN LANGSA, 2023)
The phenomenon of parents abandoning their children due to adultery is quite common these days. In the marriage legal system in Indonesia, children born outside a legal marriage cannot be recognized as legitimate children, so their civil aspects follow those of their mother. Children resulting from adultery lose some of their rights as children of a father, and this has the potential to disrupt their future. This research aims to analyze the rights of children resulting from adultery and whether there are solutions that can be taken so that children resulting from adultery still receive their rights even without a cross-breed relationship with their biological father. The research method used is a library research with a sociological-legal approach. Data sources were obtained from the law and several important articles related to this research problem. Apart from that, this article also uses the results of empirical research to strengthen the arguments in this research. Based on the research results, it was found that, from various studies, there is often a neglect of children's rights as a result of adulterous relationships. Men tend to leave their partners, and in the end, women often become single parents to meet the child's needs. Legally, the state can punish the adulterer (biological father) for being responsible for the needs of the child resulting from his adultery.